The Growth of Multi-Academy Trusts in England: Emergent Structures and the Sponsorship of Underperforming Schools. (January 2021) - Simon, Catherine A; James, Chris; Simon, Alan
In England, schools are able to take on academy status, which is intended by the central government to give them greater autonomy (DfE, 2018). Groups of academies can form multi-academy trusts (MATs), which typically grow in size with additional schools becoming academies and joining. One mechanism for MAT growth is sponsorship, which occurs when an underperforming school is required to become an academy and to join a MAT to facilitate its improvement. It was to explore the emerging patterns of MATs and their operation, especially in relation to sponsorship, that the research we report here was carried out. The research was conducted in two phases. In the first phase, we sought to establish the emerging patterns of MATs that sponsor underperforming schools. In the second phase, we interviewed MAT chief executive officers (CEOs) to further explore emerging patterns of MATs, the factors affecting the growth of MATs and the nature of sponsorship. Our analysis shows the development of a complex and potentially unsustainable state schooling system in England, managed by Regional School Commissioners (RSCs) and dependent on the altruistic values and motivations of CEOs of MATs to improve schools that are underperforming.